(untitled) (Journal of Universal Science Research, 2023)
this article presents the results of a study of the incidence structure of acute appendicitis based on the collection of statistics from the archives of the Surkhandarya branch of the Republican Scientific Center for Emergency Medical Care (SBRSCEMC) and Central hospital of Termez city (CHTC) of Termez.